PROFILE OF CHRONIC HEPATITIS B IN LIVER AND NON LIVER MALIGNANCIES AT DR. SAIFUL ANWAR MALANG GENERAL HOSPITAL - Tandya, Renny; Rakhman, M. Farid; Mustika, Syifa (Jurnal Ners, 2023)
Background: Hepatitis B virus (HBV) infection is a worldwide problem associated with morbidity and mortality. Hepatitis B virus (HBV) was identified as a major risk factor for carcinoma, one of them is associated with hepatocellular carcinoma. Aim: This study aims to determine the profile of hepatitis B patients with malignancy at the Gastroenterohepatology Outpatient Polyclinic at Saiful Anwar Regional General Hospital. Methods: This research is an observational study with a cross-sectional design. Data was collected from 2013 to 2018. The chronic hepatitis B patients were found in the Gastroenterohepatology polyclinic. Data was collected in the form of secondary data, including patient demographic data including age, sex, and type of drug. The results are described descriptively and presented in tables/percentages. Results: From the results of the study, the total number of chronic hepatitis B patients with malignancy in was 218 people. Most of the patients were aged 20-60 years with an average age of 49.7 ± 12.6 years. Most of the subjects were male, 78.0%. Most of the therapy given to patients was tenofovir 300 mg (93.2%). Cases were dominated by liver malignancy (52.8%). Most of the patients who had non-liver malignancy were diagnosed with ca mammae (37.0%). Conclusion: Chronic hepatitis B virus infection may have the potential to damage liver tissue which can lead to malignancy. The prevalence of liver and non-liver malignancies in chronic hepatitis B patients in this study were 52.8% and 47.3%, respectively.